2018
DOI: 10.1038/s41416-018-0210-y
|View full text |Cite
|
Sign up to set email alerts
|

Irradiance controls photodynamic efficacy and tissue heating in experimental tumours: implication for interstitial PDT of locally advanced cancer

Abstract: Background Currently delivered light dose (J/cm 2 ) is the principal parameter guiding interstitial photodynamic therapy (I-PDT) of refractory locally advanced cancer. The aim of this study was to investigate the impact of light dose rate (irradiance, mW/cm 2 ) and associated heating on tumour response and cure. Methods Finite-element modeling was used to compute intratumoural irradiance and dose to guide Photofrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 39 publications
2
40
0
Order By: Relevance
“…In a recent preclinical light dose‐finding study for Photofrin ® ‐mediated I‐PDT, we demonstrated the importance of irradiance in obtaining tumor control and cures in the treatment of locally advanced cancers with Photofrin ® . In the study reported here, we further demonstrated the importance of irradiance during Photofrin ® ‐mediated I‐PDT by treating mice with FEM‐simulated subtherapeutic and therapeutic irradiances.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…In a recent preclinical light dose‐finding study for Photofrin ® ‐mediated I‐PDT, we demonstrated the importance of irradiance in obtaining tumor control and cures in the treatment of locally advanced cancers with Photofrin ® . In the study reported here, we further demonstrated the importance of irradiance during Photofrin ® ‐mediated I‐PDT by treating mice with FEM‐simulated subtherapeutic and therapeutic irradiances.…”
Section: Discussionsupporting
confidence: 58%
“…It is important to note that at 160 and 200 mW cm −1 , cures were obtained in both mice treated with Photofrin ® and mice treated with light only. We previously reported that at our effective light regimen for Photofrin ® ‐mediated I‐PDT with simultaneous light illumination, light‐induced tissue heating to temperatures ≥60°C (thermal ablation) occurred . In that study, this thermal ablation alone, although less effective than Photofrin ® ‐mediated I‐PDT, resulted in some cures (up to 40%) when treating locally advanced SCCVII.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations